Disability assist dogs in public places - experiences from trainers and handlers in Aotearoa New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Master in Public Health at Massey University, Palmerston North, Aotearoa New Zealand - McManus, Bronwyn Sarah (Massey University, 2021)
Disability assist dogs are trained to support people with a variety of impairments. Aside from performing tasks that benefit their handlers, their presence is considered a catalyst for social interactions. Previous studies have consistently reported the positive benefits of such interactions, which increase disabled handlers' quality of life. However, there is limited research and literature that has explored the enabling and disabling impacts on the dog/handler team of expected and unexpected interactions with members of the public. These repeated, prolonged or unwanted interactions may create further barriers for disabled people to participate and gain full inclusion in community life. This research aimed to explore the experiences of handlers and trainers of disability assist dogs in terms of the types of interactions they had with members of the Aotearoa New Zealand (NZ) public and how these interactions were perceived, interpreted, and managed. A qualitative method, guided by an interpretive approach and social constructionism, was utilised to collect data via semi-structured interviews with six handlers and six trainers of disability assist dogs. Data were analysed using thematic analysis with the social model of disability as the theoretical base. Four themes were identified: (1) every day a new experience, (2) enabling interactions, (3) disabling interactions, and (4) role of ambassador. Findings indicated that handlers regularly faced a complex range of unique interactions due to various reasons such as the public's ambivalence or lack of knowledge and understanding of the dog's role and right of access to public places. While handlers may face friendly comments about the dog and its role, these encounters could also involve long conversations, invasive personal questions, interference with their dogs, and denied access into businesses, cafes, restaurants, and public transport. These findings underpin the need to provide more education to the public on the etiquette of engaging with handlers and their disability assist dogs and more support for businesses to understand the legal rights of handlers. Through more education and support to change societal attitudes and remove structural barriers, disabled people using disability assist dogs will be able to independently participate in community life and be fully included without hindrance.
Keywords: 420318 People with disability